Strategi Komunikasi Dosen dan Mahasiswa dalam Proses Pembelajaran: Studi Kasus pada Program Studi Pendidikan Administrasi Perkantoran Universitas Negeri Makassar: (STUDI KASUS PADA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN UNIVERSITAS NEGERI MAKASSAR) - Nasir, Nasir; Asmansyah (STISIP Widyapuri Mandiri Sukabumi, 2026)
Communication is an important element in the learning process in higher education because it determines the success of material delivery and student involvement. However, in practice, there are still various communication obstacles between lecturers and students that have an impact on learning effectiveness. This study aims to describe the communication strategies of lecturers and students in the learning process and identify the factors that support and hinder the effectiveness of academic communication in the Office Administration Education Study Program, State University of Makassar. This research uses a qualitative approach with a case study type of research. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Data analysis is carried out by the stages of data reduction, data presentation, and drawing conclusions and verification. The results of the study showed that lecturers applied communication strategies through the use of clear language, a variety of learning methods, providing feedback, and the creation of a dialogical classroom atmosphere. Students show communication strategies through participation in discussions, expressions of opinions, and responses to learning materials, although there are still some students who are passive. Communication interactions tend to be two-way, but under certain conditions, one-way communication is still found. Factors supporting communication effectiveness include lecturer openness, student motivation, and conducive classroom atmosphere, while inhibiting factors include differences in communication skills and limited learning time. This research contributes to the development of communication science and education by providing an understanding of the importance of communication strategies in improving the quality of learning in higher education.